The dual role of polyethylene glycol-simulated drought stress in Stevia rebaudiana (Bertoni): growth reduction and integrated physiological, biochemical, and steviol glycoside responses - Shafiq Hussain; Mehran Ali; Muhammad Zahid; Simone Ribeiro Lucho; Caroline Dambroz; Joyce Dória (Physiology and Molecular Biology of Plants, 2026)
Stevia rebaudiana Bertoni is a globally recognized natural sweetener owing to its zero-calorie steviol glycosides (SGs). However, drought stress, one of the leading abiotic constraints to crop productivity, adversely affects stevia growth and development, while simultaneously altering its biochemical composition. This review highlights the impact of polyethylene glycol (PEG)-induced drought stress on stevia, with particular emphasis on agronomic traits, metabolites, antioxidant activities, and SGs biosynthesis. PEG-mediated stress reduces key growth parameters, such as plant height, biomass, and leaf area, but in some cases, it promotes root elongation as an adaptive strategy to optimize water uptake. Such alterations are accompanied by biochemical adjustments, notably the up-regulation of antioxidant enzymes, such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), which neutralize reactive oxygen species (ROS)-induced oxidative stress. Moreover, PEG stress enhances the accumulation of secondary metabolites, such as phenolic, flavonoids and terpenoids, thereby improving antioxidant potential and stress tolerance. Notably, PEG-induced drought stress shapes SG biosynthesis through the up-regulation of the methylerythritol phosphate (MEP) pathway and the differential expression of key SG-related genes. Such modulation frequently increases SG accumulation, thereby strengthening their medicinal and economic value. Overall, this review covers the dual nature of PEG-induced drought stress: while limiting agronomic performance, enhances SGs biosynthesis and antioxidant capacity. Gaining insights into these mechanisms will facilitate the development of optimized cultivation strategies under water deficit conditions. Future research should prioritize molecular breeding and advanced biotechnological approaches to enhance drought tolerance and maximize the production of bioactive metabolites in stevia.